Urban areas in rural landscapes – the importance of green space and local architecture for bat conservation - Printz, Lisa; Jung, Kirsten (Frontiers in Ecology and Evolution, 2023)
Urbanization is a highly disperse process, resulting in urban sprawl across landscapes. Within such landscapes, structural heterogeneity may be an important factor for maintaining biodiversity. We investigated the importance of habitat heterogeneity on bats in villages across the Schwäbische Alb, Germany, a progressively urbanized region. Bat activity and diversity were assessed using acoustic monitoring. We characterized habitat composition at the local and neighborhood scale and assessed environmental characteristics of urban density, vegetation cover and architectural features, combining satellite and ground-based measures. Our results revealed that the composition of the neighborhood determines the occurrence different bat species, while local spatial, structural, and architectonic parameters at recording sites affected bat activity, feeding activity and social encounters. An increased proportion of impervious surfaces and newly constructed housing areas were associated with fewer bat species and lower bat activity. Bat activity, feeding and social encounters were highest in housing areas constructed between 1950-2000 and increased with higher proportions of older, rather openly structured vegetation. Our results clearly show a combined importance of neighborhood and local conditions affecting habitat suitability and quality of rural urban areas for bats. This highlights that strategies for biodiversity inclusion in rural urban planning need to consider both local and neighborhood conditions to support bat diversity and vital bat activity and exemplifies future challenges maintaining biodiversity within progressively urbanized rural landscapes, as this needs support by municipalities to maintain space for nature in areas for urban development and the consciousness by local residents for biodiversity-friendly modernizations.